Burnout among labour inspectors in Greece: A nationwide cross-sectional study. (March 2021) - Anyfantis, I.D.; Papagiannis, D.; Rachiotis, G.
Highlights: Labour inspectors are exposed to psychosocial and organizational risks, that could cause burnout. High rates of burnout and a plethora of work-related contributing risk factors were identified. A supportive and protective framework, can significantly reduce the levels of experienced burnout. The lack of legal protection was reported to be a major shortcoming and a stress factor. Abstract: The principal role of labour inspectorates is labour law enforcement and compliance, to secure effective implementation of legal provisions relating to the protection of workers. These aspects can turn the job context of a labour inspector into a really demanding occupation, that may have significant physiological and psychological effects. The aim of this study is to investigate the prevalence of burnout between labour inspectors in Greece and associated factors. A semi-structured survey was conducted covering job characteristics, perceived job limitations, some associated with economic crisis, and a burnout assessment tool. There were 102 responses collected out of the 245 labour inspectors specialised in occupational safety and health. Two out of three inspectors (67.65%) reported that reduction of their salary resulted by austerity measures, affected their work quality and performance, 92% reported that job demands had significantly increased during the previous year and 55% that their work does not provide the flexibility, while NLI's framework does not provide support in performing their job related tasks. Our study identified high rates of burnout and a plethora of work-related contributing risk factors such as increased job demands, lack of staff and resources. The establishment of an effective work framework, that would be supportive and protective for inspectors, in a top-down approach, promoting interpersonal relations and providing the necessary degrees of freedom to labour inspectors' tasks, could significantly reduce the levels of experienced burnout.